AL HIJÂMAH SEBAGAI WASILAH DAKWAH - Dewi Mustika (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
The teaching of the heavens (Islam) has been earthed through the angel Gabriel to the Prophet Muhammad sallallaahu 'alayhi wa Salam. With the derivation of the Holy Qur'an as a source of guidance, guidance, and strength for Muslims throughout the world. Through the Qur'an and Sunnah of the Prophet, Islam has given a teaching to man towards a healthy life both inward and inward. Not a few hadiths of Rasulullah SAW that contain medical values ​​that we need to emulate today in the field of Islamic medicine. Among the words of the Prophet sallallaahu 'alayhi wa Salam commanded the ummah to berbekam. The research method that the writer uses is analytical descriptive method, with library research, in this research only described some concept of Rasulullah implicit in books of hadith that peel health problem, the work of scholars and medical experts. Then the author of the analysis by synergizing the methods and concepts of modern medicine today. Hope the Muslims can return to the treatment given by the Apostle which is loaded with the values ​​of da'awi namely the Divine based medicine, ilmiyah and alamyah in this century. This research is still in the form of a global depiction, so it still requires in-depth and detailed assessment in its subtans. So that later could really become enlightenment for the Muslims in living this life.